DevR PCR for the Diagnosis of Intraocular Tuberculosis. (February 2015) - Kataria, Pankaj; Kumar, Abiraj; Bansal, Reema; Sharma, Aman; Gupta, Vishali; Gupta, Amod; Singh, Ramandeep; Sharma, Kusum
Abstract Purpose: To compare the efficacy of devR and MPB64 PCR in the diagnosis of intraocular tuberculosis. Methods: Prospective, nonrandomized study. Seventy-five patients were enrolled in 3 groups. Group A had 25 patients with presumed intraocular tubercular uveitis, group B had 25 controls with specific uveitis other than tubercular uveitis, and group C included 25 non-uveitic negative controls. The undiluted vitreous/aqueous samples were collected and subjected to PCR assay for devR and MPB64 gene sequence of Mycobacterium tuberculosis (MTB) to detect sensitivity and specificity. Results: devR PCR was positive in 16 (64%) out of 25 patients with presumed tubercular uveitis. MPB64 PCR was positive in 18 (72%) out of 25 patients with presumed tubercular uveitis. The sensitivity and specificity of devR were 64 and 100%, respectively. The sensitivity and specificity of MPB64 PCR were 72 and 100%, respectively. Conclusion: devR PCR is not a better tool than MPB64 PCR for diagnosing intraocular tuberculosis.